Understanding patient partnership in health systems: lessons from the Canadian patient partner survey. Issue 9 (7th September 2022) - Abelson, Julia; Canfield, Carolyn; Leslie, Myles; Levasseur, Mary Anne; Rowland, Paula; Tripp, Laura; Vanstone, Meredith; Panday, Janelle; Cameron, David; Forest, Pierre-Gerlier; Sussman, Daniel; Wilson, Geoff
Abstract : Objectives: To examine the sociodemographic characteristics, activities, motivations, experiences, skills and challenges of patient partners working across multiple health system settings in Canada. Design: Online cross-sectional survey of self-identified patient partners. Setting: Patient partners in multiple jurisdictions and health system organisations. Participants: 603 patient partners who had drawn on their experiences with the health system as a patient, family member or informal caregiver to try to improve it in some way, through their involvement in the activities of a group, organisation or government. Results: Survey respondents predominantly identified as female (76.6%), white (84%) and university educated (70.2%) but were a heterogeneous group in the scope (activities and organisations), intensity (number of hours) and longevity (number of years) of their role. Primary motivations for becoming a patient partner were the desire to improve the health system based on either a negative (36.2%) or positive (23.3%) experience. Respondents reported feeling enthusiastic (83.6%), valued (76.9%) and needed (63.3%) always or most of the time; just under half felt they had always or often been adequately compensated in their role. Knowledge of the health system and the organisation they partner with are key skills needed. Two-thirds faced barriers in their role with over half identifying power imbalances. Less than half were able to see how their input was reflected in decisions or changes always or most of the time, and 40.3% had thought about quitting. Conclusions: This survey is the first of its kind to examine at a population level, the characteristics, experiences and dynamics of a large sample of self-identified patient partners. Patient partners in this sample are a sociodemographically homogenous group, yet heterogeneous in the scope, intensity and longevity of roles. Our findings provide key insights at a critical time, to inform the future of patient partnership in health systems.